Dampak Kualitas Air Terhadap Kelangsungan Hidup Ikan Bandeng (Chanos chanos) di Tambak Area Bekas Pabrik Peleburan Aki - Faizzah, Nurul; Putri, Marsha Savira Agatha; Wicaksono, Rizky Rahadian; Hanif, Muhammad; Ni’am, Achmad Chusnun; Yanik, Carri Noer Fida (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2025)
In Pucuk District, Lamongan Regency, there is pond aquaculture around the battery smelting plant. In this case, of course, the pond needs good water quality. The purpose of this study is to determine the quality of pond water in accordance with the Quality Standards of Government Regulation of the Republic of Indonesia (PP RI) No. 22 of 2021 Class III Water. And to find out the Effect of Water Quality on the Survival Rate of Milkfish (Chanos chanos). The method used in this study is Observation. This study was carried out for 14 days, namely on day 0, day 7 and day 14 for water quality measurement and monitoring of milkfish survival rate. The parameters observed include pH, Temperature, DO, TSS, COD, Pb. The research time is from April 2024 to May 2024. The research sample was taken from 2 pond locations, namely on the west side of the factory with a distance of 2 meters and behind the factory with a distance of 5 meters. Sampling is determined by the distance between the factory and the pond which is the closest location because no waste disposal outlet is found. The results of the effect of water quality on the survival rate of milkfish (Chanos chanos) were analyzed using SPSS 21 Linear Regression. Based on the results of measuring pH, Temperature, and DO parameters from day 0, day 7 to day 14, the value meets the quality standard. And for the TSS and Pb parameters, the 0th day exceeded the quality standard, then on the 7th to the 14th day the TSS and Pb values decreased until they met the quality standard. And for the COD parameter from day 0, day 7 to day 14, the value decreased but still exceeded the quality standard. So it can be known that the pond water in this study has a risk of decreasing water quality which can have an impact on the health of milkfish.